'NetAccess': Networked access to computerized-system using Iris - M. Kadhum, Mohammed; Ali, Musab A. M.; Hassan, Suhaidi (IEEE Computer Society, 2009)
Based on the available secured files and information in the companies; they need to be secured by a very high system. Currently, most of companies are accessed by normal keys in order to access the offices. But, those keys might be lost or stolen. In addition, those doors can be hacked easily by thieves. This raises a need to improve security of such information by limiting access only to those who have authorization to do so. The traditional means, as well as biometric traits other than iris, do provide such control; yet they still have several limitations in verifying the identity of individuals. In this presents the design of an Iris Recognition System for accessing Building and Control System